2001
DOI: 10.1097/00003246-200106000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Role of central nervous system nitric oxide in the development of neurogenic pulmonary edema in rats

Abstract: Neurogenic pulmonary edema is characterized by elevated pulmonary vascular permeability and may be inhibited by nitric oxide production in the medulla oblongata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The massive centrally mediated ␣-adrenergic discharge involves neuronal populations (nuclei reticularis gigantocellularis and parvicellularis) in the medulla that cause generalized vasoconstriction and high pulmonary vascular pressures that result in enhanced transcapillary fluid migration in the alveolar bed (1). In experimental animal models, endothelins and nitric oxide have been implicated as important mediators in the pathogenesis of neurogenic pulmonary edema (23,24). We observed significant increases in lung water content in our model at 48 hrs following MCAO, both in animals that received no intravenous fluids as well as in those that were maintained on isotonic fluids (1.0 -1.5 mL/ kg/hr of 0.9% saline).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The massive centrally mediated ␣-adrenergic discharge involves neuronal populations (nuclei reticularis gigantocellularis and parvicellularis) in the medulla that cause generalized vasoconstriction and high pulmonary vascular pressures that result in enhanced transcapillary fluid migration in the alveolar bed (1). In experimental animal models, endothelins and nitric oxide have been implicated as important mediators in the pathogenesis of neurogenic pulmonary edema (23,24). We observed significant increases in lung water content in our model at 48 hrs following MCAO, both in animals that received no intravenous fluids as well as in those that were maintained on isotonic fluids (1.0 -1.5 mL/ kg/hr of 0.9% saline).…”
Section: Discussionmentioning
confidence: 56%
“…The precise mechanisms of this egress of water from the lungs with an induced hyperosmolar state cannot be inferred from our study. Although the potent diuretic action may be a ready explanation for attenuation of lung water content with mannitol, we postulate that it may involve up-regulation of aquaporins in the pulmonary bed (24,25) as well, particularly with HS therapy.…”
Section: Discussionmentioning
confidence: 89%
“…Although the precise mechanism of this observation remains elusive at present, it is postulated that the massive centrally mediated ␣-adrenergic discharge from selective neuronal populations in the medulla causes generalized vasoconstriction and high pulmonary vascular pressures resulting in enhanced transcapillary fluid migration in the alveolar bed (44). Endothelins and nitric oxide have been implicated as important mediators in the pathogenesis of neurogenic pulmonary edema (45,46). We observed significant increases in lung water content in our model at 24, 48, 72, and 96 hrs following MCAO in animals that received isotonic fluids (1 mL/kg/hr of NS).…”
Section: Discussionmentioning
confidence: 99%
“…Its onset is rapid, often inducing cardiac and respiratory failure; therefore, the mortality rates are high (10). In recent years, the incidence of acute pulmonary edema has gradually increased (3).…”
Section: A B C D Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that the antioxidant capacity and associated SOD enzyme activity of the lung tissue significantly decreased when the duration of pulmonary edema was extended; whereas the levels of the MDA lipid peroxidation product significantly increased, and the levels of IL-6 in the plasma and lung tissue significantly increased, which suggested that the induction of oxidative stress may have an important role in the pulmonary tissue damage associated with acute pulmonary edema. Furthermore, the alterations in the levels of the MDA, SOD and IL-6 oxidative stress-related indices in the lung tissue of rats with hypoxia suggested that the pathogenesis of acute pulmonary edema is complicated, and may be a result numerous factors (25,26).…”
Section: A B C D Discussionmentioning
confidence: 99%